Physiological monitoring and monitoring of health-saving activity in the process of physical education of students - L. V. Kapilevich; V. G. Shil’ko; A. V. Kabachkova (Бюллетень сибирской медицины, 2011)
The enhancement of physical education of students under conditions of humanization of education assumes, first, the organization of monitoring, which is a part of the education process and is oriented at the permanent observation, evaluation, analysis, and correction of this process and its results. Second, the results of the monitoring are the starting point for the projection, formation, and correction of the education process through the change of its conditions such as the introduction of differentiation in the need in students’ sport exercises and level differentiation in the degree of formation of motivation to exercises, methodic and physical efficiency. The gathering of combined information about indices of physical education of students will allow the optimization of the efficiency and correction of used physical education programs.